HUBUNGAN TUMOR MARKER CA-125 DENGAN SIFAT DAN TIPE SEL TUMOR OVARIUM DI RSUD ARIFIN ACHMAD PEKANBARU - Tryanda Ferdyansyah; Amru Sofian; Fatmawati " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Ovarian tumor caused by inflammation or proliferation of ovarian’s ephitelial, germinal, stroma cell and it can be benign and malignant. Ovarian tumor had many tumor markers, the most known is Cancer Antigen 125 (CA-125). The normal concentration of CA-125 is <35 IU/ml. CA-125 could be used to predict a malignancy with cut off value ≥35 IU/ml. However, some benign conditions can be found with value ≥35 IU/ml, and some malignancy conditions with normal CA-125 concentration. The purpose of this research was to know correlation between CA-125 with the ovarians tumor malignancy and cell type. This research used retrospective design which involving 206 samples. The characteristic and cell type was based on histopathologycal examination and the value of CA-125 was based on clinical pathology laboratory test result. From 136 patients with benign ovarian tumor, 80 (57,5%) with CA-125 was still in normal limit and 59 (42,5%) was increased. From 67 patients with malignant ovarian tumor, 23 (34,3%) with CA-125 was still in normal limit and 44 (65,7%) was increased. This research showed there was a significant correlation between tumor marker CA-125 with the ovarians tumor malignancy (p =0,002), ephitelial cell type (p=0,001), and germinal cell type (p=0,001).Key words : ovarian tumor, ovarian tumor marker, Cancer Antigen 125, ovarian tumors malignancy and cell type